Navicula subphyllepta sp. nov. (Naviculaceae, Bacillariophyceae), a new brackish diatom species from France - Contamine, Léa; Beauger, Aude; Voldoire, Olivier; Ragot, Angèle; Vijver, Bart Van De (Phytotaxa, 2025)
A new brackish-water diatom species, Navicula subphyllepta Contamine, Beauger & Van de Vijver sp. nov., is described from a managed canal in the Marais Poitevin (Vendée, western France). This taxon was initially misidentified as Navicula phyllepta Kützing, but detailed morphological analysis using light and scanning electron microscopy revealed significant differences in valve dimensions, stria density, and ultrastructural features of the central area and raphe system. The new species was dominant in a pelagic sample from a moderately alkaline site characterized by high conductivity and elevated sulfate and bromide concentrations, reflecting a strong brackish influence. Navicula subphyllepta is compared to similar species, including 1205527114 N. phyllepta, N. phylleptosoma, N. salinarum, and N. lindae, from which it is clearly separated by a combination of morphometric and structural features. The new species is observed seasonally in both planktonic and benthic assemblages. Its description contributes to the growing recognition of taxonomic diversity in brackish diatom floras, which remain understudied in Western Europe.